Correlation between p38 mitogen-activated protein kinase and human telomerase reverse transcriptase in sarcomas - Matsuo, Toshihiro (BioMed Central, 2012)
BACKGROUND: One of the major components of telomerase is the human telomerase reverse transcriptase (hTERT) as the catalytic protein. hTERT mRNA expression are reported to be associated with prognosis and tumor progression in several sarcomas. However, there is no clear understanding of the mechanisms of hTERT in human sarcomas. Recent studies have suggested that signals transmitted through p38 mitogen-activated protein kinase (MAPK) can increase or decrease hTERT transcription in human cells. The purpose of this study was to analyse the correlation between p38 MAPK and hTERT in sarcoma samples. METHODS: We investigated 36 soft tissue malignant fibrous histiocytomas (MFH), 24 liposarcomas (LS) and 9 bone MFH samples for hTERT and p38 MAPK expression. Quantitative detection of hTERT and p38 MAPK was performed by RT-PCR. RESULTS: There was a significant positive correlation between the values of hTERT and p38 MAPK in all samples (r = 0.445, p = 0.0001), soft tissue MFH (r = 0.352, p = 0.0352), LS (r = 0.704, p = 0.0001) and bone MFH samples (r = 0.802, p = 0.0093). Patients who had a higher than average expression of p38 MAPK had a significantly worse prognosis than other patients (p = 0.0036). CONCLUSIONS: p38 MAPK may play a role in up-regulation of hTERT, and therefore, p38 MAPK may be a useful marker in the assessment of hTERT and patients' prognosis in sarcomas.